Community-based treatment of onchocerciasis with ivermectin: acceptability and early adverse reactions. - Pacque, M. C. (World Health Organization, 1989)
A study of community-based treatment of onchocerciasis with ivermectin was undertaken in a rain forest area of Liberia to investigate the possible occurrence of serious adverse effects. The total population was 13,704, the microfilarial load was 5.35 mf/mg skin, and the prevalence of Onchocerca volvulus infection was 50% at 9 years of age and over 80% among those aged 15 years and older. Certain groups (like pregnant women and young children) were excluded from treatment. Out of the 7956 people eligible for treatment, 7699 (97%) accepted the ivermectin. Data on possible adverse reactions were collected by four different methods, including systematic house-by-house follow-up visits three days after treatment, biweekly population surveillance, and monitoring of both mobile clinic records and hospital records. No severe adverse reactions were noted, and no deaths could be related to ivermectin treatment; only 1.3% of the persons treated had a moderate adverse reaction of the Mazzotti type, presumably related to the killing of microfilariae. The study showed good acceptance by the population, and that mass treatment campaigns with ivermectin are feasible.